2006
DOI: 10.1007/s00431-006-0371-1
|View full text |Cite
|
Sign up to set email alerts
|

From hyperinsulinaemic hypoglycaemia to ketotic hypoglycaemia: the range of glucose abnormalities in patients born with intrauterine growth retardation

Abstract: Newborns with a history of IUGR and HH have an increased risk of developing ketotic hypoglycaemia in the childhood period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…These patients present early in life with severe ketoacidosis that results in lethargy, vomiting, and coma, requiring aggressive intravenous hydration, bicarbonate, and glucose and insulin therapy (20,62,105,143,149,181,192,210). Some CoA transferase-deficient patients also present with hypoglycemia, and CoA transferase deficiency may contribute to a subset of idiopathic ketotic hypoglycemia cases (20,27,52,83,92,108). If maintained on carbohydrate-rich diets that are mildly reduced in protein content, CoA transferase-deficient patients seem to thrive, albeit with persistent hyperketonemia.…”
Section: Ketone Body Metabolismmentioning
confidence: 97%
“…These patients present early in life with severe ketoacidosis that results in lethargy, vomiting, and coma, requiring aggressive intravenous hydration, bicarbonate, and glucose and insulin therapy (20,62,105,143,149,181,192,210). Some CoA transferase-deficient patients also present with hypoglycemia, and CoA transferase deficiency may contribute to a subset of idiopathic ketotic hypoglycemia cases (20,27,52,83,92,108). If maintained on carbohydrate-rich diets that are mildly reduced in protein content, CoA transferase-deficient patients seem to thrive, albeit with persistent hyperketonemia.…”
Section: Ketone Body Metabolismmentioning
confidence: 97%
“…In accordance, it has been suggested that these children have no metabolic abnormalities but rather represent the end of the Gaussian curve for fasting tolerance in children due to accelerated starvation (7,8). In contrast, it has been reported that children born small for gestational age who develop transient neonatal hyperinsulinemic hypoglycemia can present later in childhood with ketotic hypoglycemia (9). This indicates a more complex metabolic or endocrine underlying cause, at least in some patients.…”
Section: Discussionmentioning
confidence: 90%
“…Given that relatively short duration diazoxide therapy (3−4 months) was effective for most and no surgical intervention was required, those treated for hyperinsulinism likely met the criteria for an entity called 'prolonged neonatal hyperinsulism' (7,10). Moreover, many of our infants had risk factors for 'prolonged neonatal hyperinsulinism' which included early preterm birth, male sex, intrauterine growth restriction, or birth asphyxia (7,(11)(12)(13). Infants with this disorder were first described in 1984; however, it was Hoe et al in 2006, who created this diagnostic category (7).…”
Section: Discussionmentioning
confidence: 99%